Bullinger en die verbond na aanleiding van die Tweede Switserse Konfessie - Botha, Schalk Jacobus (Hervormde teologiese studies, 1985)
Bullinger's concept of the covenant and the Confessio Helvetica Posterior The Confessio Helvetica Posterior is not only one of the most extensive confessions of the Reformed churches but it is also very widely accepted. The composer of the confession was JH Bullinger (1504—1575) who was one of the first, if not the first. Reformer to make use of the concept of the covenant in his theological thinking, Bullinger's specific idea of a bilateral or conditional covenant is most probably unprecedented in Christian Thought and in this respect he not only differed from Calvin but he also initiated another tradition in reformed Protestantism. Basically the Confessio Helvetica Posterior is nothing else than an unfolding of Bullinger's concept of the covenant.